Perception of Loneliness in Adolescence: Role of Maladaptive Personality Traits and Trauma-Related Symptomatology - Fiorenza Giordano; Danilo Calaresi; Valeria Saladino; Valeria Verrastro (Brain Sciences)
Background/Objectives: Loneliness is a heterogeneous phenomenon, generally defined as an emotional experience based on the perceived distance between an individual’s actual social relationships and those he or she would like to have. Adolescence is particularly vulnerable to loneliness because of the many changes in values, feelings, and emotions that characterize it. Among the aspects that may influence this feeling of discomfort, the literature identifies maladaptive personality and a dysfunctional response to traumatic events. Our study aims to identify the possible role that maladaptive personality traits and post-traumatic stress symptomatology in the form of Post-Traumatic Stress Disorder (PTSD) and Disturbance in Self-Organization (DSO) may play in the perception of loneliness in adolescents: Methods: We identified a mediation model constructed through structural equation modeling (SEM) to test PTSD and DSO post-traumatic stress symptomatology as independent variables and maladaptive personality as a mediator in the relationship between these and perceptions of loneliness in a population of adolescents of both sexes, Italian high school students; Results: Our study identifies the significant role of PTSD and DSO symptomatology in influencing the state of loneliness, both directly and indirectly through maladaptive personality traits, which appear to exert a substantial influence on the perception of loneliness, potentially functioning as mediators in the relationship between the latter and PTSD/DSO symptomatology. Presumably, a maladaptive personality may complicate recovery from adverse and traumatic experiences by preventing the implementation of functional coping strategies and promoting dysfunctional responses. Conclusions: Our findings underscore the importance of researchers and clinicians adequately considering different personality traits and the early identification of post-traumatic stress symptomatology. A focus on adolescents’ communication and interpersonal skills and their ability to respond effectively to stressful and traumatic events may prove useful in identifying more effective strategies for preventing and managing loneliness and related distress in adolescents.